Trip13 Depletion in Liver Cancer Induces a Lipogenic Response Contributing to Plin2‐Dependent Mitotic Cell Death. Issue 29 (28th August 2022) - Rios Garcia, Marcos; Meissburger, Bettina; Chan, Jessica; de Guia, Roldan M.; Mattijssen, Frits; Roessler, Stephanie; Birkenfeld, Andreas L.; Raschzok, Nathanael; Riols, Fabien; Tokarz, Janina; Giroud, Maude; Gil Lozano, Manuel; et al.
Abstract: Aberrant energy metabolism and cell cycle regulation both critically contribute to malignant cell growth and both processes represent targets for anticancer therapy. It is shown here that depletion of the AAA+‐ATPase thyroid hormone receptor interacting protein 13 (Trip13) results in mitotic cell death through a combined mechanism linking lipid metabolism to aberrant mitosis. Diminished Trip13 levels in hepatocellular carcinoma cells result in insulin‐receptor‐/Akt‐pathway‐dependent accumulation of lipid droplets, which act as functional acentriolar microtubule organizing centers disturbing mitotic spindle polarity. Specifically, the lipid‐droplet‐coating protein perilipin 2 (Plin2) is required for multipolar spindle formation, induction of DNA damage, and mitotic cell death. Plin2 expression in different tumor cells confers susceptibility to cell death induced by Trip13 depletion as well as treatment with paclitaxel, a spindle‐interfering drug commonly used against different cancers. Thus, assessment of Plin2 levels enables the stratification of tumor responsiveness to mitosis‐targeting drugs, including clinically approved paclitaxel and Trip13 inhibitors currently under development. Abstract : A novel mechanism is presented by which depletion of the ATPase thyroid hormone receptor interacting protein 13 (Trip13) results in mitotic cell death, including enhanced lipogenesis and a role of lipid droplet accumulation in aberrant mitotic spindle polarity. Specifically, perilipin 2 confers susceptibility to Trip13‐knockdown‐ and antimitotic‐drug‐induced cell death, allowing for stratification for paclitaxel‐treatment‐responsive tumor cells.